Detection of Clostridium difficile toxin genes by PCR: sequence variation may cause false-negative results. Issue 2 (February 2015) - Cao, Bo; Zhang, Yuanyuan; Bian, Funing; Cheng, Ying; Wang, Jing; Jia, Hongbing; Zhang, Wen; Lu, Jinxing; Chen, Chen; Du, Pengcheng
Abstract : Abbreviations: CDI, C. difficile infection; PaLoc, pathogenicity locus; SNP, single nucleotide polymorphism.